1995
DOI: 10.1021/bi00005a023
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Conformational Changes of Thymidylate Synthase Detected by Limited Proteolysis

Abstract: Limited tryptic proteolysis was used to investigate conformational changes of thymidylate synthase from Lactobacillus casei induced by ligand binding. Most of the identified sites of proteolysis were between R72 and R178, a region that includes a large loop containing residues 90-139 that is absent in thymidylate synthase from most other sources. Hydrolysis at both ends of this region was affected by the presence of dUMP. With dUMP, the preference of initial hydrolysis at the N-terminus of this region was swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is well documented that upon formation of either the catalytic or the inhibitory ternary complex, the enzyme, particularly its Cterminal residues, undergoes a major conformational shift that is stabilized by a hydrogen bonding network involving the folate co-substrate (1). Indeed, this shift alters the susceptibility of TS to proteolytic enzymes in vitro (15). It is therefore not surprising that the conformational change stabilizes the enzyme in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that upon formation of either the catalytic or the inhibitory ternary complex, the enzyme, particularly its Cterminal residues, undergoes a major conformational shift that is stabilized by a hydrogen bonding network involving the folate co-substrate (1). Indeed, this shift alters the susceptibility of TS to proteolytic enzymes in vitro (15). It is therefore not surprising that the conformational change stabilizes the enzyme in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…One important mechanism is the disruption of the autoregulatory feedback loop for the repression of translation. TS ligands, such as 5-FU, disrupt the binding of the TS enzyme with TYMS mRNA, leading to translational derepression and overproduction of the TS enzyme. ,, In addition to translational derepression, enzyme stabilization has been suggested as the primary mechanism of TS induction by fluoropyrimidines in human CRC and ovarian cancer cell lines. − Furthermore, it is proposed that fluoropyrimidine-mediated increases in TS levels are induced by its effect on TS enzyme stability, with no effect on TYMS mRNA. ,, The amplification of TYMS , leading to the overproduction of TYMS mRNA and TS protein, is another mechanism of resistance to fluoropyrimidines like 5-FU and its derivatives . These observations indicated that an understanding of translational derepression, enzyme stabilization, and gene amplification as the process of TS induction can help to elucidate the mechanism of the acquisition of 5-FU resistance.…”
Section: Discussionmentioning
confidence: 99%
“…27−29 Furthermore, it is proposed that fluoropyrimidine-mediated increases in TS levels are induced by its effect on TS enzyme stability, with no effect on TYMS mRNA. 28,30,31 The amplification of TYMS, leading to the overproduction of TYMS mRNA and TS protein, is another mechanism of resistance to fluoropyrimidines like 5-FU and its derivatives. 12 These observations indicated that an understanding of translational derepression, enzyme stabilization, and gene amplification as the process of TS induction can help to elucidate the mechanism of the acquisition of 5-FU resistance.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Furthermore, it is proposed that fluoropyrimidine-mediated increases in TS levels occur through an effect on enzyme stability with no effect on its mRNA [25,27]. It is also suggested that TS stabilization could be the result of conformational changes that may occur upon the formation of a ternary complex, reducing the susceptibility of the TS enzyme to proteolysis [28]. These findings indicated that understanding translational derepression and enzyme stabilization as the process of TS induction has significance for elucidating the mechanism of resistance acquisition.…”
Section: Discussionmentioning
confidence: 99%